2012
DOI: 10.2298/mpns1206238s
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of incidence and treatment of pneumothorax in five-year period in Kragujevac

Abstract: The results of study show similarities with other studies regarding both the incidence of certain forms of pneumothorax and the gender-age profile of patients and their treatment, taking into account the observed period and the target population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The study of Spasic et al [32] in Serbia, although unclear, showed a certain degree of relationship between climate and PSP.…”
Section: Pollutants and Meteorological Parametersmentioning
confidence: 90%
“…The study of Spasic et al [32] in Serbia, although unclear, showed a certain degree of relationship between climate and PSP.…”
Section: Pollutants and Meteorological Parametersmentioning
confidence: 90%